Perovskite thin film and preparation method and application thereof
Patent Information
- Application Number
- CN202310787823.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-06-30
AI Technical Summary
[0005]为了解决现有技术中的钙钛矿薄膜的整体缺陷态密度及界面电荷传输能力仍然不能使钙钛矿电池器件的效率和稳定性满足商业要求的技术问题,本发明提供了一种钙钛矿薄膜的制备方法
[0018]本发明提供了一种钙钛矿薄膜及其制备方法与应用,在FA0.90MA0.03Cs0.07Pb(I0.92Br0.08)3钙钛矿薄膜的制备方法中采用包含羰基和三苯胺的添加剂三苯胺基苯甲酸,所述三苯胺基苯甲酸中的羰基能与钙钛矿溶液中配位不足的Pb2+离子结合,或者是与其他缺陷态的阳离子结合,降低钙钛矿膜缺陷密度,此外,三苯胺基团与羰基基团形成高的静电势,导致钝化剂小分子电荷分离能力增强,有利于进一步增强添加剂的钝化效果,减少晶粒表面的缺陷,提高钙钛矿矿薄膜的质量和稳定性;含有羰基和三苯胺两功能基团,添加剂可增强钙钛矿层与空穴传输层之间的空穴传输能力、低缺陷态使钙钛矿薄膜更加稳定,减少了外界水氧侵蚀薄膜的入口,添加剂通过防止水和氧气损坏活性层,可以有效增强器件的稳定性。试验结果证明,本发明提供的制备方法得到的FA0.90MA0.03Cs0.07Pb(I0.92Br0.08)3钙钛矿薄膜的缺陷密度低于5,将其作为钙钛矿吸光层制备钙钛矿太阳能电池,电池的光电转换效率达到23%左右。
Smart Images

Figure BDA0004312828420000071 
Figure BDA0004312828420000081
Abstract
Description
Technical Field
[0001] This invention relates to the field of perovskite thin film technology, and particularly to a perovskite thin film, its preparation method, and its application. Background Technology
[0002] With the increasing severity of global energy shortages and environmental degradation, countries around the world are seeking green and renewable energy sources to replace traditional fossil fuels. Solar energy, as a new type of clean energy that is inexhaustible, holds the promise of replacing traditional fossil fuels. Currently, organic-inorganic hybrid perovskites, as a new generation of photovoltaic materials, exhibit excellent photoelectric properties as light-absorbing materials, such as high absorption coefficients and long carrier diffusion distances, thus demonstrating unique advantages in photovoltaic devices. Perovskite solar cells (PVSCs) have become one of the current research hotspots in the photovoltaic field. To date, due to the unique photoelectric properties of perovskite materials and the joint efforts of scientists, the photoelectric conversion efficiency of perovskite solar cells has exceeded 26%, making them a promising next-generation commercial photovoltaic technology.
[0003] However, the commercialization of perovskite solar cells still requires solving many problems. For example, perovskite films prepared under low-temperature solution conditions have a large number of defects, especially at their surface and interfaces, where a large number of uncoordinated atoms form, resulting in a large number of defect states at the perovskite surface and interface, mainly electron-deficient defects Pb. 2+ This results in significant interface charge transport losses, impacting the efficiency and long-term stability of perovskite solar cells and hindering their practical application. Therefore, various strategies are needed to improve the growth quality of perovskite thin films to enhance the long-term stability of perovskite solar cells. Among these, additive engineering strategies, by regulating perovskite grain growth and reducing the defect density of the perovskite film, have become an effective strategy for improving the stability of perovskite solar cells.
[0004] Among numerous additives, carbonyl functional materials have proven to be effective passivation materials for fabricating high-efficiency and stable perovskite solar cells. However, the overall defect state density of the modified perovskite film still falls short of commercially viable photoelectric efficiency and stability requirements when using existing carbonyl functional materials to modify perovskite materials. Therefore, to advance the commercialization of perovskite solar cells, it is imperative to mitigate the negative impact of density defects in the perovskite film structure on device efficiency and stability. Summary of the Invention
[0005] To address the technical problem that the overall defect state density and interfacial charge transport capability of existing perovskite thin films still cannot meet the efficiency and stability requirements of perovskite solar cell devices for commercial use, this invention provides a method for preparing perovskite thin films.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0007] The main objective of this invention is to provide a method for preparing perovskite thin films. This method involves adding additives containing carbonyl and triphenylamine groups to a perovskite precursor solution, stirring and heating to obtain a modified perovskite precursor solution; and then using a spin-coating method to spin-coat the modified perovskite precursor solution onto FTO conductive glass to obtain FA. 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3 Perovskite thin film, wherein FA is formamidinium ion and MA is methylammonium ion;
[0008] The additive is triphenylaminobenzoic acid; the concentration of the additive in the perovskite precursor solution is 0.01-5 mg / ml, the stirring and heating temperature is 20-60℃, and the time is 1-48 h.
[0009] Furthermore, the concentration of the additive in the perovskite precursor solution is 0.1-2.5 mg / ml, the stirring and heating temperature is 25-40℃, and the time is 6-24 h.
[0010] Further, the method for preparing the perovskite precursor solution of the present invention is as follows: formamidinium hydroiodate, methylammonium iodide, cesium iodide, ferric bromide, methylammonium chloride, lead bromide, and lead iodide are added to a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a molar ratio of 1.107 mol:0.04 mol:0.095 mol:0.108 mol:0.473 mol:0.108 mol:1.282 mol, wherein the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 200 μL:800 μL.
[0011] Further, the solution spin-coating method involves spin-coating the modified perovskite precursor solution onto FTO conductive glass at 1000 r / min for 10 s, followed by a second spin-coating at 4000 r / min for 30 s. During the last 10 s of the second spin-coating, ethyl acetate solution is dripped into the center of the FTO conductive glass at a constant rate. After the spin coating is completed, the glass is annealed on a hot stage at 100°C for 40 min. After annealing, the FTO conductive glass with the perovskite film is cooled to obtain FA. 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Perovskite thin films.
[0012] Furthermore, the method for preparing the FTO conductive glass is as follows: cleaning the FTO conductive substrate glass, spin-coating the cleaned substrate glass with a tin dioxide precursor solution, and then annealing it in an air atmosphere to obtain an FTO conductive glass with a SnO2 electron transport layer.
[0013] Another objective of this invention is to provide a FA prepared by the above-described preparation method of this invention. 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Perovskite thin films.
[0014] Finally, the present invention will prepare the FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Application of perovskite thin films as perovskite light-absorbing layers in the fabrication of perovskite solar cells.
[0015] Furthermore, the FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3. A perovskite thin film is used as the perovskite light-absorbing layer, and a Spiro-OMeTAD precursor solution is spin-coated on the perovskite light-absorbing layer. A hole transport layer is deposited on the perovskite light-absorbing layer, and finally a silver electrode is evaporated to obtain a perovskite solar cell.
[0016] Furthermore, the preparation method of the Spiro-OMeTAD precursor solution is as follows: Spiro-OMeTAD, 4-tert-butylpyridine and lithium bis(trifluoromethanesulfonyl)imide solution are dissolved in acetonitrile, and then mixed with chlorobenzene at 30°C and stirred until dissolved to obtain the Spiro-OMeTAD precursor solution.
[0017] Furthermore, when spin-coating the Spiro-OMeTAD precursor solution, the rotation speed was 4000 r / min, the acceleration was 4000 r / min, and the time was 30 s.
[0018] This invention provides a perovskite thin film, its preparation method, and its application, in FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 The preparation method of perovskite thin films uses triphenylaminobenzoic acid, an additive containing carbonyl and triphenylamine. The carbonyl group in the triphenylaminobenzoic acid can react with the insufficiently coordinated Pb in the perovskite solution.2+ Ion bonding, or bonding with cations of other defect states, reduces the defect density of the perovskite film. Furthermore, the high electrostatic potential formed by the triphenylamine and carbonyl groups enhances the charge separation ability of small passivating agent molecules, further enhancing the passivation effect of the additive, reducing surface defects, and improving the quality and stability of the perovskite film. Containing both carbonyl and triphenylamine functional groups, the additive enhances hole transport between the perovskite layer and the hole transport layer. The low defect state makes the perovskite film more stable, reducing the entry point for external water and oxygen erosion. By preventing water and oxygen from damaging the active layer, the additive effectively enhances the stability of the device. Experimental results demonstrate that the FA obtained by the preparation method provided in this invention... 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3. The defect density of the perovskite thin film is less than 5. When it is used as a perovskite light-absorbing layer to prepare perovskite solar cells, the photoelectric conversion efficiency of the cells reaches about 23%. Detailed Implementation
[0019] This invention discloses a perovskite thin film, its preparation method, and its applications. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired results. It is particularly important to note that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included within this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0020] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below with reference to specific embodiments.
[0021] Example 1: Preparation of FTO conductive glass
[0022] Cleaning FTO glass substrate:
[0023] The FTO conductive substrate glass was cleaned in an ultrasonic cleaner by sequentially adding alkaline cleaning solution, deionized water, acetone, and ethanol for 30 minutes. After cleaning, it was dried with a hair dryer and then pretreated in an ozone ion cleaner (UV-Ozone) for 30 minutes.
[0024] Deposit a SnO2 electron transport layer on the pretreated substrate:
[0025] To prepare the SnO2 precursor solution, pipette 200 μL of commercial SnO2 into a beaker, then add 800 μL of deionized water and stir to mix thoroughly.
[0026] The SnO2 precursor solution was spin-coated onto FTO glass at a speed of 3000 r / min for 30 s, and then annealed in air at 150 °C for 30 min to obtain the SnO2 electron transfer layer. After annealing, the solution was allowed to cool naturally and then treated again in an ozone ion cleaner for 30 min. The solution was then ready for use.
[0027] The present invention can also use other preparation methods to prepare FTO conductive glass, as long as the SnO2 electron transfer layer can be spin-coated onto the FTO conductive substrate glass to obtain FTO conductive glass with SnO2 electron transfer layer.
[0028] Example 2FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Preparation of perovskite thin films
[0029] Preparation of FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Titanium ore precursor solution:
[0030] Weigh out formamidin hydroiodate, methylammonium iodide, cesium iodide, ferric bromide, methylammonium chloride, lead bromide, and lead iodide, with a molar ratio of 1.107 mol: 0.04 mol: 0.095 mol: 0.108 mol: 0.473 mol: 0.108 mol: 1.282 mol, and add to a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide to obtain FA. 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 The precursor of 3-titanium dioxide, N,N-dimethylformamide and dimethyl sulfoxide, was prepared in a volume ratio of 200 μL:800 μL. The FA obtained above... 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3 Triphenylaminobenzoic acid was added to the perovskite precursor. The amount of the additive was 0.5 mg / ml of the perovskite precursor solution. The precursor solution was stirred and heated at 30℃ for 12 h.
[0031] Spin coating FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br0.08 3. Perovskite light-absorbing layer:
[0032] 50 μL of the modified perovskite precursor solution was pipetted onto the FTO conductive glass prepared in Example 1 at 1000 rpm for 10 s, followed by spin coating at 4000 rpm for 30 s. During the last 10 s of the second spin coating, 300 μL of ethyl acetate solution was pipetted into the center of the FTO at a constant rate. After spin coating, the glass was annealed on a hot plate at 100 °C for 40 min. After annealing, the FTO conductive glass was removed and allowed to cool naturally to obtain FA. 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Perovskite thin films.
[0033] Example 3FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Preparation of perovskite thin films
[0034] Preparation of FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3) Perovskite precursor solution:
[0035] Weigh out formamidinium hydroiodate, methylammonium iodide, cesium iodide, ferric bromide, methylammonium chloride, lead bromide, and lead iodide in a molar ratio of 1.107 mol: 0.04 mol: 0.095 mol: 0.108 mol: 0.473 mol: 0.108 mol: 1.282 mol. Add a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 200 μL: 800 μL. Add triphenylaminobenzoic acid as an additive to the precursor solution at a concentration of 2.5 mg / mL of the perovskite precursor solution. Stir and heat the precursor solution at 40 °C for 6 h.
[0036] Spin coating FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3 Perovskite light-absorbing layer;
[0037] 50 μL of the perovskite precursor solution was pipetted onto the FTO conductive glass prepared in Example 1 at 1000 rpm for 10 s using a spin coater, followed by spin coating at 4000 rpm for 30 s. In the last 10 s of the second step, 300 μL of ethyl acetate solution was pipetted into the center of the FTO at a constant rate. After spin coating, the glass was annealed on a hot plate at 100°C for 40 min. After annealing, the FTO conductive substrate glass was removed and allowed to cool naturally to obtain the desired perovskite light-absorbing layer.
[0038] Example 4FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Preparation of perovskite thin films
[0039] Preparation of FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Titanium ore precursor solution:
[0040] Weigh out formamidinium hydroiodate, methylammonium iodide, cesium iodide, ferric bromide, methylammonium chloride, lead bromide, and lead iodide in a molar ratio of 1.107 mol: 0.04 mol: 0.095 mol: 0.108 mol: 0.473 mol: 0.108 mol: 1.282 mol. Add a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 200 μL: 800 μL. Add triphenylaminobenzoic acid as an additive to the precursor solution at a concentration of 0.1 mg / mL of the perovskite precursor solution. Stir and heat the precursor solution at 25 °C for 24 h.
[0041] Spin coating FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3 Perovskite light-absorbing layer;
[0042] 50 μL of the perovskite precursor solution was pipetted onto the FTO conductive glass prepared in Example 1 at 1000 rpm for 10 s using a spin coater, followed by spin coating at 4000 rpm for 30 s. In the last 10 s of the second step, 300 μL of ethyl acetate solution was pipetted into the center of the FTO at a constant rate. After spin coating, the glass was annealed on a hot plate at 100°C for 40 min. After annealing, the FTO conductive substrate glass was removed and allowed to cool naturally to obtain the desired perovskite light-absorbing layer.
[0043] Example 5FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Preparation of perovskite thin films
[0044] Preparation of FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3) Perovskite precursor solution:
[0045] Weigh out formamidinium hydroiodate, methylammonium iodide, cesium iodide, ferric bromide, methylammonium chloride, lead bromide, and lead iodide in a molar ratio of 1.107 mol: 0.04 mol: 0.095 mol: 0.108 mol: 0.473 mol: 0.108 mol: 1.282 mol. Add a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 200 μL: 800 μL. Add triphenylaminobenzoic acid as an additive to the precursor solution at a concentration of 0.05 mg / mL of the perovskite precursor solution. Stir and heat the precursor solution at 20 °C for 48 h.
[0046] Spin coating FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3 Perovskite light-absorbing layer;
[0047] 50 μL of the perovskite precursor solution was pipetted onto the FTO conductive glass prepared in Example 1 at 1000 rpm for 10 s using a spin coater, followed by spin coating at 4000 rpm for 30 s. In the last 10 s of the second step, 300 μL of ethyl acetate solution was pipetted into the center of the FTO at a constant rate. After spin coating, the glass was annealed on a hot plate at 100°C for 40 min. After annealing, the FTO conductive substrate glass was removed and allowed to cool naturally to obtain the desired perovskite light-absorbing layer.
[0048] Example 6FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Preparation of perovskite thin films
[0049] Preparation of FA 0.90 MA 0.03 Cs0.07 Pb(I 0.92 Br 0.08 3. Titanium ore precursor solution:
[0050] Weigh out formamidinium hydroiodate, methylammonium iodide, cesium iodide, ferric bromide, methylammonium chloride, lead bromide, and lead iodide in a molar ratio of 1.107 mol: 0.04 mol: 0.095 mol: 0.108 mol: 0.473 mol: 0.108 mol: 1.282 mol. Add a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 200 μL: 800 μL. Add triphenylaminobenzoic acid as an additive to the precursor solution at a concentration of 1.25 mg / mL of the perovskite precursor solution. Stir and heat the precursor solution at 60 °C for 1 h.
[0051] Spin coating FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3 Perovskite light-absorbing layer;
[0052] 50 μL of the perovskite precursor solution was pipetted onto the FTO conductive glass prepared in Example 1 at 1000 rpm for 10 s using a spin coater, followed by spin coating at 4000 rpm for 30 s. In the last 10 s of the second step, 300 μL of ethyl acetate solution was pipetted into the center of the FTO at a constant rate. After spin coating, the glass was annealed on a hot plate at 100°C for 40 min. After annealing, the FTO conductive substrate glass was removed and allowed to cool naturally to obtain the desired perovskite light-absorbing layer.
[0053] Example 7FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Preparation of perovskite thin films
[0054] Preparation of FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Titanium ore precursor solution:
[0055] Weigh out formamidinium hydroiodate, methylammonium iodide, cesium iodide, ferric bromide, methylammonium chloride, lead bromide, and lead iodide in a molar ratio of 1.107 mol: 0.04 mol: 0.095 mol: 0.108 mol: 0.473 mol: 0.108 mol: 1.282 mol. Add a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 200 μL: 800 μL. Add triphenylaminobenzoic acid as an additive to the precursor solution at a concentration of 0.01 mg / mL of the perovskite precursor solution. Stir and heat the precursor solution at 40 °C for 36 h.
[0056] Spin coating FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3 Perovskite light-absorbing layer;
[0057] 50 μL of the perovskite precursor solution was pipetted onto the FTO conductive glass prepared in Example 1 at 1000 rpm for 10 s using a spin coater, followed by spin coating at 4000 rpm for 30 s. In the last 10 s of the second step, 300 μL of ethyl acetate solution was pipetted into the center of the FTO at a constant rate. After spin coating, the glass was annealed on a hot plate at 100°C for 40 min. After annealing, the FTO conductive substrate glass was removed and allowed to cool naturally to obtain the desired perovskite light-absorbing layer.
[0058] Example 8FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Preparation of perovskite thin films
[0059] Preparation of FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Titanium ore precursor solution:
[0060] Weigh out formamidinium hydroiodate, methylammonium iodide, cesium iodide, ferric bromide, methylammonium chloride, lead bromide, and lead iodide in a molar ratio of 1.107 mol: 0.04 mol: 0.095 mol: 0.108 mol: 0.473 mol: 0.108 mol: 1.282 mol. Add a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 200 μL: 800 μL. Add triphenylaminobenzoic acid as an additive to the precursor solution at a concentration of 5 mg / mL of the perovskite precursor solution. Stir and heat the precursor solution at 40 °C for 12 h.
[0061] Spin coating FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3 Perovskite light-absorbing layer;
[0062] 50 μL of the perovskite precursor solution was pipetted onto the FTO conductive glass prepared in Example 1 at 1000 rpm for 10 s using a spin coater, followed by spin coating at 4000 rpm for 30 s. In the last 10 s of the second step, 300 μL of ethyl acetate solution was pipetted into the center of the FTO at a constant rate. After spin coating, the glass was annealed on a hot plate at 100°C for 40 min. After annealing, the FTO conductive substrate glass was removed and allowed to cool naturally to obtain the desired perovskite light-absorbing layer.
[0063] Example 9: Fabrication of Perovskite Solar Cells
[0064] Spiro-OMeTAD (72.3 mg), 4-tert-butylpyridine (28.8 μL), and lithium bis(trifluoromethanesulfonyl)imide (17.5 μL) solution, along with 520 mg of lithium bis(trifluoromethanesulfonyl)imide, were dissolved in 1 mL of acetonitrile and mixed with chlorobenzene (1 mL). The mixture was placed on a magnetically heated stirring table and stirred at 30 °C until dissolved to obtain the Spiro-OMeTAD precursor solution. 40 μL of the prepared Spiro-OMeTAD precursor solution was taken using a pipette and spin-coated onto the perovskite light-absorbing layer prepared in Examples 2-5 using a spin coater at a rotation speed of 4000 r / min and an acceleration of 4000 r / min for 30 s. The prepared substrate was then placed in a vacuum deposition apparatus to deposit silver electrodes at a vacuum degree of 1 × 10⁻⁶. -5 Pa, current 90A, complete the fabrication of perovskite solar cells.
[0065] Effect Comparison
[0066] In Example 2, the additive triphenylaminobenzoic acid was replaced with 4-carboxyphenyl isothiocyanate, 6-aminonicotinic acid, 4-carboxybutyraldehyde, 4-phenylbenzoic acid, methyl biphenyl-4-carboxylate, and methyl methacrylate in Comparative Examples 1-6 of Table 1, respectively. No additives were added in Comparative Example 7. The other preparation steps and parameters of Comparative Examples 1-7 were the same as those in Example 2, and the perovskite films prepared in Comparative Examples 1-7 were obtained. Then, the perovskite films prepared in Examples 2-8 and Comparative Examples 1-7 were characterized and tested. The test data of the thickness, roughness, average particle size, and defect density of the perovskite films of each example and comparative example are shown in Table 1.
[0067] Table 1. Test data for thickness, roughness, average grain size, and defect density of perovskite thin films.
[0068]
[0069]
[0070] The perovskite thin films prepared in Examples 2-5 and Comparative Examples 1-7 were used to fabricate perovskite solar cells, using the same preparation method as in Example 6. The photoelectric response of the fabricated perovskite solar cells was tested under the AM 1.5G solar spectrum. The test results are shown in Table 2.
[0071] Table 2 Test parameters for various perovskite solar cells
[0072] Example 2 24.04% 1.153V <![CDATA[25.31mA / cm 2 ]]> 82.38% Example 3 23.84% 1.151V <![CDATA[25.24mA / cm 2 ]]> 82.07% Example 4 23.71% 1.147V <![CDATA[25.26mA / cm 2 ]]> 81.86% Example 5 23.74% 1.150V <![CDATA[25.21mA / cm 2 ]]> 81.92% Example 6 23.65% 1.148V <![CDATA[25.19mA / cm 2 ]]> 81.78% Example 7 23.48% 1.144V <![CDATA[25.11mA / cm 2 ]]> 81.74% Example 8 23.45% 1.143V <![CDATA[25.15mA / cm 2 ]]> 81.61% Comparative Example 1 22.23% 1.135V <![CDATA[24.33mA / cm 2 ]]> 80.45% Comparative Example 2 22.25% 1.139V <![CDATA[24.24mA / cm 2 ]]> 80.59% Comparative Example 3 22.19% 1.141V <![CDATA[24.19mA / cm 2 ]]> 80.41% Comparative Example 4 22.08% 1.133V <![CDATA[24.15mA / cm 2 ]]> 80.71% Comparative Example 5 22.07% 1.133V <![CDATA[23.95mA / cm 2 ]]> 81.35% Comparative Example 6 21.79% 1.139V <![CDATA[23.76mA / cm 2 ]]> 80.46% Comparative Example 7 21.57% 1.123V <![CDATA[23.86mA / cm 2 ]]> 80.51%
[0073] Tables 1 and 2 show that the perovskite film prepared by the method provided in this invention reduces the defect density of the perovskite film and yields higher FA. 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 The defect density of the perovskite film is less than 5, which enhances the passivation effect of the additive, thereby improving the quality and stability of the perovskite film. Simultaneously, the low defect state makes the perovskite film more stable, further enhancing the stability of the device. (FA) 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3 Perovskite thin film was used as a perovskite light-absorbing layer to prepare perovskite solar cells, and the photoelectric conversion efficiency of the cells reached about 23%.
[0074] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a perovskite thin film, characterized in that, Additives containing carbonyl and triphenylamine groups were added to the perovskite precursor solution and stirred and heated to obtain the modified perovskite precursor solution. The modified perovskite precursor solution was spin-coated onto FTO conductive glass using a solution spin-coating method to obtain FA. 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3 Perovskite thin film, wherein FA is formamidinium ion and MA is methylammonium ion; The additive is triphenylaminobenzoic acid; the concentration of the additive in the perovskite precursor solution is 0.01-5 mg / ml, the stirring and heating temperature is 20-60℃, and the time is 1-48 h.
2. The preparation method according to claim 1, characterized in that, The concentration of the additive in the perovskite precursor solution is 0.1-2.5 mg / ml, the stirring and heating temperature is 25-40℃, and the time is 6-24 h.
3. The preparation method according to claim 1, characterized in that, The perovskite precursor solution is prepared by adding formamidinium hydroiodate, methylammonium iodide, cesium iodide, ferric bromide, methylammonium chloride, lead bromide, and lead iodide to a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide in a molar ratio of 1.107 mol:0.04 mol:0.095 mol:0.108 mol:0.473 mol:0.108 mol:1.282 mol, wherein the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 200 μL:800 μL.
4. The preparation method according to claim 1, characterized in that, The solution spin-coating method is as follows: The modified perovskite precursor solution is spin-coated onto FTO conductive glass at 1000 r / min for 10 s, followed by a second spin-coating at 4000 r / min for 30 s. During the last 10 s of the second spin-coating, ethyl acetate solution is dripped into the center of the FTO conductive glass at a constant rate. After the spin coating is completed, the glass is annealed on a hot plate at 100°C for 40 min. After annealing, the FTO conductive glass with the perovskite film is cooled to obtain FA. 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Perovskite thin films.
5. The preparation method according to claim 1, characterized in that, The method for preparing the FTO conductive glass is as follows: cleaning the FTO conductive substrate glass, spin-coating the cleaned substrate glass with a tin dioxide precursor solution, and then annealing it in an air atmosphere to obtain FTO conductive glass with a SnO2 electron transport layer.
6. The FA prepared by the preparation method according to any one of claims 1-5 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 3. Perovskite thin films.
7. The application of the perovskite thin film as described in claim 6 as a perovskite light-absorbing layer in the fabrication of perovskite solar cells.
8. The application as described in claim 7, characterized in that, The FA 0.90 MA 0.03 Cs 0.07 Pb(I 0.92 Br 0.08 )3. A perovskite thin film is used as the perovskite light-absorbing layer, and a Spiro-OMeTAD precursor solution is spin-coated on the perovskite light-absorbing layer. A hole transport layer is deposited on the perovskite light-absorbing layer, and finally a silver electrode is evaporated to obtain a perovskite solar cell.
9. The application as described in claim 8, characterized in that, The preparation method of the Spiro-OMeTAD precursor solution is as follows: Spiro-OMeTAD, 4-tert-butylpyridine and lithium bis(trifluoromethanesulfonyl)imide solution are dissolved in acetonitrile, and then mixed with chlorobenzene at 30°C and stirred until dissolved to obtain the Spiro-OMeTAD precursor solution.
10. The application as described in claim 8, characterized in that, When spin-coating the Spiro-OMeTAD precursor solution, the rotation speed was 4000 r / min, the acceleration was 4000 r / min, and the time was 30 s.
Citation Information
Patent Citations
Perovskite precursor solution, preparation method thereof and perovskite solar cell
CN114141953A